Analisis Kepatuhan dalam Penatalaksanaan DM Tipe II Dimasa Pandemi Covid-19 - Tintin Sumarni; Yulastri Yulastri; Novi Herawati; Abd Gafar (Jurnal Gema Keperawatan, 2023)
The prevalence of diabetes mellitus (DM) in Indonesia has increased significantly. Diabetes mellitus is a non-communicable disease reported to be suffered by some Covid-19 patients. DM patient non-compliance in implementing the five pillars results in an increased risk of complications, especially during the Covid-19 pandemic. The purpose of this study was to determine the adherence of type II DM patients in the management of the five pillars of DM. This study used a descriptive analytic cross sectional approach. The sampling technique was total sampling, namely type II DM sufferers who visited Posbindu in the work area of the Solok City Health Center in the last 3 months involving 65 people, the instrument used was a questionnaire with diet variables, taking medication, doing physical activity, education and controlling blood sugar. The results showed that medication adherence, diet, education and blood sugar control had a significant relationship with blood sugar levels with a p value of less than 0.05. It turned out that what was most dominantly related to blood sugar levels was the regularity of taking medication with (p value 0,002) OR= 72,500. This non-compliance is because the client perceives that blood sugar that is not normal means that he has recovered from DM. It is hoped that diabetes mellitus clients can understand the importance of implementing DM management. There is a policy from the Health Service involving family members to care for, so that the five pillars of management of DM can be implemented properly, so that DM patients can live a life without complications.